2021
DOI: 10.1111/aej.12600
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the calcium silicate‐based cement–composite interface and the bonding strength with total‐etch or single/two‐stage self‐etch adhesive systems

Abstract: Due to favourable biological and physical properties, calcium silicate‐based cements (CSCs) are biocompatible materials used widely for vital pulp therapies. Sealing efficacy between the adhesive system and CSC determines the clinical success of treatment. This study aimed to evaluate the shear bond strength (SBS) of CSC to composite resin with different adhesive systems and to analyse the CSC–composite interface. Mineral trioxide aggregate (MTA) (ProRoot MTA; Dentsply Tulsa Dental, Tulsa, OK), Biodentine (Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 33 publications
(78 reference statements)
0
7
0
2
Order By: Relevance
“…Therefore, as Figure 1 search flowchart demonstrates, 5 studies were included for qualitative data synthesis. [20][21][22][23][24] In Table 1, the literature search findings are outlined.…”
Section: Search Results Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, as Figure 1 search flowchart demonstrates, 5 studies were included for qualitative data synthesis. [20][21][22][23][24] In Table 1, the literature search findings are outlined.…”
Section: Search Results Findingsmentioning
confidence: 99%
“…The quality assessment results using the "Modified CONSORT checklist of items for reporting in vitro studies of dental materials" (Faggion, 2012) 15 are presented in Table 2. From a total of 5 studies assessed, 4 studies had results between 50% and 60% in terms of the quality of the data reported in their respective papers, [20][21][22][23] while the study by Xavier et al 24 had the highest quality assessment report at 70%. All the articles presented a well-summarized abstract, specific background, and explanation of rationale, as well as clear objectives and/or hypotheses (items 1, 2a and 2b).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…17 KS simanlar ve adeziv sistemler arasında bağlanma gücü, vital pulpa tedavisinin başarısını doğrudan etkiler. 10 Restoratif tedavinin uzun süreli başarısı için biyomateryaller ile restoratif materyal arasındaki bağın kalitesi hayati önem taşımaktadır. KS simanlar ile kompozit rezin arasındaki düzgün stres dağılımı biyomateryal ve kompozit rezinin fizikokimyasal özelliklerine ayrıca ara yüzeyi oluşturan adeziv sistem tipine de bağlıdır.…”
Section: Anahtar Keli̇melerunclassified
“…Biodentin'e, hızlandırıcı olarak kalsiyum klorür eklenmiş ve sertleşme süresi 12 dakika olarak bildirilmiştir. 10 Kalsiyum silikat esaslı hidrofilik simanların toz-likit ile karıştırılması sırasında heterojen kıvam dezavantajının üstesinden gelmek için önceden karıştırılmış trikalsiyum silikat esaslı simanlar piyasaya sürülmüştür. 11 Son zamanlarda, hem Biodentin hem de MTA'nın klinik uygulamalarını paylaşan kullanıma hazır pat halinde yeni biomateryal NeoPutty (NuSmile, Houston, TX, USA) geliştirilmiştir.…”
Section: Gereç Ve Yöntemunclassified